2010
DOI: 10.1007/s11920-010-0167-x
|View full text |Cite
|
Sign up to set email alerts
|

Common Factors in Empirically Supported Treatments of Borderline Personality Disorder

Abstract: In this article, we examine the manuals of empirically supported psychotherapies for borderline personality disorder (BPD) by comparing their common and specific treatment strategies. We compare these treatments using a previously constructed scale of treatment interventions. Individual psychotherapies for BPD have several common strategies: clear treatment framework, attention to affect, focus on treatment relationship, an active therapist, and exploratory and change-oriented interventions. Use of interpretat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 38 publications
2
51
0
5
Order By: Relevance
“…In these cases, the goal should be to refer a student, if possible, to a clinician practicing one of the empirically supported psychotherapies, including DBT, mentalization-based therapy (MBT), schema-focused therapy (SFT), general psychiatric management (GPM), transference-focused therapy (TFP), or systems training for emotional predictability and problem solving (STEPPS). All these treatments have common strategies including: clear treatment framework, attention to the patient's affective state, focus on the treatment relationship, an active therapist, and exploratory and change-oriented interventions (Weinberg et al, 2011). Indeed, some authorities have suggested that the empirically-based treatments for BPD have more similarities than differences (Paris, 2010).…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…In these cases, the goal should be to refer a student, if possible, to a clinician practicing one of the empirically supported psychotherapies, including DBT, mentalization-based therapy (MBT), schema-focused therapy (SFT), general psychiatric management (GPM), transference-focused therapy (TFP), or systems training for emotional predictability and problem solving (STEPPS). All these treatments have common strategies including: clear treatment framework, attention to the patient's affective state, focus on the treatment relationship, an active therapist, and exploratory and change-oriented interventions (Weinberg et al, 2011). Indeed, some authorities have suggested that the empirically-based treatments for BPD have more similarities than differences (Paris, 2010).…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…Forskning viser at behandling uten definerte rammer og varighet resulterer i at 67 % av pasientene med emosjonelt ustabil personlighetsforstyrrelse falt ut av behandlingen kort tid etter oppstart. Stort fokus på struktur og klare rammebetingelser er således viktige forutsetninger for å arbeide med denne pasientgruppen (Derksen, Benders & Roverts 1998, Weinberg, Ronningstam, Goldblatt, Schechter, Maltsberger, 2011.…”
Section: Innledningunclassified
“…This suggests that common factors explain part of the efficacy of treatment, with structure being particularly important. 21 A clearer understanding of what parts of these complex interventions are most important may lead to refinements of treatment and potential cost savings. The most recent Cochrane review of psychotherapy for borderline personality disorder, although it included only studies published to 2003, found support for dialectical behaviour therapy and mentalization-based treatment, 22 and recent findings strengthen this conclusion.…”
Section: Is Admission To Hospital Helpful?mentioning
confidence: 99%